Pedagogical characteristics of the systems for assessing the technical and tactical skills of qualified volleyball players - Олійник, Михайло; Дорошенко, Едуард (Slobozhanskyi Herald of Science and Sport, 2017)
Мykhailo Oliinyk & Eduard Doroshenko Purpose: on the basis of the analysis of the special literature and their own experimental studies, to determine the characteristics of the systems for assessing the technical and tactical skills of qualified volleyball players. Material & Methods: study was conducted on the basis of the material of the national team of Zaporozhye State Medical University on volleyball. Analysis and generalization of the data of scientific and methodical literature are used; registration, analysis and interpretation of indicators of technical and tactical actions of qualified volleyball players in training and competitive processes; pedagogical observations; algorithms for calculating the quantitative and qualitative indicators of technical and tactical skill in volleyball; methods of mathematical statistics. Results: data on the existence of a strong statistical relationship between the systems of assessment of technical and tactical skills of qualified volleyball players, taking into account the specificity of the game role. Conclusion: shows the specifics of the application of various systems for assessing the technical and tactical skills of qualified volleyball players, taking into account the factors of the game role, noted the methodological features of special analysis and interpretation of indicators of technical and tactical actions in the adversarial process.